Children’s Sports Physiology—The Early Studies - Pantelis T. Nikolaidis; Daniel A. Marinho; Vicente Javier Clemente-Suárez; Valentine D. Son’kin (Physiologia, 2023)
The purpose of this editorial is to summarize the main findings of early studies in the field of children’s sports physiology [...]